Adult Age-Structure Variability in an Amphibian in Relation to Population Decline - Middleton, Jessica; Green, David M. (Herpetologica, 2015)
Animal populations that normally fluctuate in size in response to stochastic environmental events might be subject to unsustainably high mortality rates in the face of progressive habitat loss or degradation. This should perturb the population’s age-structure in predictable ways if the increase in mortality is age- or stage-specific (i.e., a decline in recruitment should result in a progressively older adult population, whereas a decline in adult survivorship should result in a progressively younger adult population). We used skeletochronology to ascertain the ages of adult individuals in a population of Fowler’s Toads, Anaxyrus ( =  Bufo) fowleri, over 20 yr, spanning a period of regulated population fluctuation from 1992 to 2002 and a period of sustained population decline thereafter until 2011. Age structure was similar between sexes, but was highly variable during both periods. Although there was no temporal trend detected in average age among 420 toads during the predecline period, 1992–2000, there was an increase in average age among 469 toads during the decline period, 2002–2011, with no significant change in adult survivorship. This evidence of an aging population is consistent with a reduction in recruitment in the population, related to the progressive loss of breeding habitat caused by an invasive plant, demonstrating that amphibian populations may be threatened with decline even when mortal threats to adults have not increased.